Physicochemical Characteristics of White Tea Product of PT. Perkebunan Nusantara IX (Kaligua Gardens) Pandansari Village, Paguyangan District, Brebes Regency - Ery Fatarina Purwaningtyas; Ahmad Shobib (Advance Sustainable Science, Engineering and Technology (ASSET), 2022)
White tea is a type of tea that still sounds foreign, the high price makes white tea sometimes used as a symbol of one's social status. Due to the high price, not many people consume it, so it is less popular. PT. Perkebunan Nusantara IX  (PTPN-IX) which is located at the west foot of Mount Slamet, precisely in Pandansari Paguyangan Village, Brebes Regency, Central Java, with an altitude of 1,500-2,050 meters above sea level and a temperature between 8-280 Celsius. One type of tea product PTPN-IX that has not been studied physically, chemically and its characteristics is white tea. This study aims to examine the characteristics of white tea produced by PTPN-IX in Brebes. This research was carried out at the request of the PTPN-IX, the methodology used was to test some of the core components contained in white tea, some tests were carried out 3 times and the average value was taken. The components tested included: ash content, crude fiber, Pb/Cu/Zn/Hg content, total plate count, coliform, water content, carbohydrates, protein, pectin, tannins and caffeine. The results showed that white tea produced by PTPN-IX were: ash content of 5.70%; Crude fiber 13.40% ; Pb 2.35 mg/Kg ; Cu 12.94 mg/Kg ; Zn 22.30 mg/Kg ; Hg ( negative ) ; Total plate number 1.3 x 103 efu/g ; Coliform (negative). For chemical components, the results are: water 5.65%; carbohydrates 3.9% ; 18% protein; pectin 5.85% ; tannins 5.25% ; caffeine 2.4 – 4.5